Factor Analysis on Fast-food Consumption at UTHM Pagoh - Ee, Che Chuan; Gopal Pillay , Khuneswari (Enhanced Knowledge in Sciences and Technology, 2023)
Fast food takes just a short time to be served and fast food is so tasty and has provided convenience to people when they just order and immediately get served. Despite fast-food having a high density which contains high calories and fats, a lot of people still prefer fast food and their preference for certain fast-food brands are different. The objectives of this study are to determine the nutrient content of fast food, identify the factors that influence fast-food consumption, and identify the popular fast-food brands among UTHM Pagoh. In this study, 373 students and staff from UTHM Pagoh have been selected to become the respondents of this study and an online questionnaire has been distributed to the respondents. Descriptive Analysis, Factor Analysis, Regression Analysis, and Word Cloud are the methods used to analyse the data. From the analysis, the factors of fast-food consumption among UTHM Pagoh are “price and value”, “reputation of the fast-food brand”, and “convenience of fast-food”. The factors which influence the frequency of fast-food consumption among UTHM Pagoh are Malay race, convenience, price, and service. From Word Cloud, McDonald’s is the fast-food brand that is the most preferred. This study can contribute to UTHM Pagoh students and staff to understand which factors contribute the most to fast-food consumption and the most popular fast-food brand.